1987
DOI: 10.1002/prep.19870120305
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chemical and Mechanical Properties of Double Base Propellants during Aging

Abstract: Thermal and mechanical stability of rocket and gun propellants are very important properties with regard to safety during storage and handling and to the interior ballistics behavior during combustion. However, our knowledge of how these properties are connected is poor. In order to better understand the aging behavior of double base propellants, the following properties were measured between 60 °C and 90 °C: the depletion of the stabilizers, the degradation of the molecular weights of nitrocellulose and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…It is believed that the availability of long carbon-carbon chain in the alkyl group (C 4 H 9 ) of Bu-NENA, lower viscosity, lower glass transition temperature and an oily nature of ester group contribute positively towards the better mechanical properties of gun propellant [14]. Hence, it has been found out that Bu-NENA is the unique energetic plasticizer, which increases the energetic without affecting the mechanical properties of gun propellant.…”
Section: Resultsmentioning
confidence: 98%
“…It is believed that the availability of long carbon-carbon chain in the alkyl group (C 4 H 9 ) of Bu-NENA, lower viscosity, lower glass transition temperature and an oily nature of ester group contribute positively towards the better mechanical properties of gun propellant [14]. Hence, it has been found out that Bu-NENA is the unique energetic plasticizer, which increases the energetic without affecting the mechanical properties of gun propellant.…”
Section: Resultsmentioning
confidence: 98%
“…Tensile strength, percentage elongation and flexural properties were determined in the Instron Universal Machine (Model 1185). For the determination of % compression multitubular grains having L/D = 1.0 was made and subjected to Instron machine [21]. The specification limit for the % compression is not less than 10.00 and tensile strength is not less than 100 kg f/cm 2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The addition of different copper salts caused an improvement in the mechanical properties compared with the control sample. This result might be interpreted in terms of homogeneity and good mixing of the studied propellants, which protects them from the attack by atmospheric moisture, which might cause weak points in their structure [19]. Another explanation may be connected to the suitability of the particle size of the added burning rate modifiers to fill the spaces inside the matrix of the propellant samples, as supported by an X-ray test.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the control sample has the best thermal stability compared with the other samples studied. From the mechanical parameters presented in Table 2, σ m and ε m , of propellants S1-S6, it is observed that the use of the studied modifiers led to improvements in the mechanical properties of these propellants at different temperatures (+50 and +25 °C) compared with those of the control, which is very important for good functioning of rocket motors during their use and storage [19]. Figures 2 and 3 present the relations between the maximum stress and strain of all of the samples studied at +50 and +25 °C.…”
Section: Resultsmentioning
confidence: 99%